Inverse Space Marching Method for Determining Temperature and Stress Distributions in Pressure Components - Taler, Jan; Weglowski, Bohdan; Sobota, Tomasz; Jaremkiewicz, Magdalena; Taler, Dawid (IntechOpen, 2011)
None